1999
DOI: 10.1002/jlb.66.6.930
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol-induced neutrophil apoptosis is mediated through nitric oxide

Abstract: Clinical reports indicate that acute ethanol intoxication in chronic ethanol abusers is associated with neutropenia. We hypothesize that ethanol accelerates the apoptosis of neutrophils thus decreasing the peripheral blood count of neutrophils. We studied the effect of ethanol on neutrophil apoptosis in vivo as well as in vitro. Human neutrophils harvested from healthy subjects after an alcohol drinking binge showed enhanced apoptosis (before, 0.5 ؎ 0.25 vs. after, 26.1 ؎ 2.6% apoptotic neutrophils/field). Per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 46 publications
(55 reference statements)
0
17
0
Order By: Relevance
“…Neutrophil functions such as chemotaxis and production of reactive oxygen species have previously shown to be affected by ethanol and polyphenols (Patel et al, 1996;Lu et al, 2001). Acute ETOH exposure in humans (five glasses of wine or more) induced neutrophil apoptosis (Singhal et al, 1999a), which is expected to impair neutrophil functions. In the present study, however, no significant effects on neutrophil as well as monocyte phagocytosis were observed with the different beverages suggesting that neither ETOH nor red grape-associated polyphenols were effective.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil functions such as chemotaxis and production of reactive oxygen species have previously shown to be affected by ethanol and polyphenols (Patel et al, 1996;Lu et al, 2001). Acute ETOH exposure in humans (five glasses of wine or more) induced neutrophil apoptosis (Singhal et al, 1999a), which is expected to impair neutrophil functions. In the present study, however, no significant effects on neutrophil as well as monocyte phagocytosis were observed with the different beverages suggesting that neither ETOH nor red grape-associated polyphenols were effective.…”
Section: Discussionmentioning
confidence: 99%
“…Ten milliliters of peripheral blood was collected from each donor in heparinized tubes. Neutrophils were separated by a standard technique of density-gradient centrifugation over Ficoll-Hypaque (29).…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that interleukin-2, gamma interferon, tumor necrosis factor (TNF) alpha, granulocyte-macrophage colony-stimulating factor, granulocyte colony-stimulating factor, and glucocorticoids increase the life span of neutrophils (4-6, 14, 36). On the contrary, nitric oxide generation, both endogenous and exogenous, may accelerate neutrophil apoptosis (8,29).…”
mentioning
confidence: 99%
“…43 Whether this cell death comprises apoptosis or merely necrosis, however, remains unclear. An induction of neutrophil apoptosis has also been observed using both traditional NO donors such as SNP 44 and different sources of NO such as GSNO (0.5-5 mM). 45 Blaylock et al 46 reported that GEA 3162 (10 mM) increased neutrophil apoptosis as assessed by annexin V binding to exposed phosphatidylserine (PS) at 4 and 8 h, but not at 16 h. On the other hand, the ONOO À donor, SIN-1 (1 mM), showed no significant increase in PS exposure compared to control cells, although there was a small enhancement of annexin V binding at 4 h. The effects of these two compounds were also studied by Ward et al, 10 who demonstrated that concentrations of 10-100 mM GEA 3162 and 0.3-3 mM SIN-1 enhanced caspase-dependent morphological neutrophil apoptosis at 6 and 20 h, and 30-100 mM GEA 3162 increased annexin V binding at 6 h. In contrast to Blaylock's study, however, the increase in morphological apoptosis by 10 mM GEA 3162 was not significant at 6 h, whereas Blaylock observed significant differences at just 4 h. The principal methodological difference between the two studies is in the culture conditions.…”
Section: Neutrophilsmentioning
confidence: 96%